An Analytical Framework for Risk Evaluation and Design of Infiltration Basins for Managed Aquifer Recharge - Aldo Fiori; Felipe P. J. de Barros; Alberto Bellin (Water Resources Research)
Abstract Managed Aquifer Recharge (MAR) plays an important role in improving and supplementing groundwater storage. Many natural factors, ranging from climatic conditions to soil characteristics, can impact the efficiency of an infiltration basin. Other factors, such as engineered variables, will also influence the basin performance and the risks associated with groundwater contamination. The latter depends on the interplay between the hydraulic characteristics of the system and the soil and solute properties. The design of infiltration basins has been performed so far with the main objective of mitigating the tendency of the basin to reduce the infiltration rate with time due to clogging of the basin's bottom. Less attention has been paid to the risk of groundwater contamination by the infiltrating water. To understand the complex interplay between natural and engineering parameters on MAR efficiency and the contamination risk, we propose a risk‐oriented analytical framework. The framework allows to investigate the interplay between soil parameters, engineering design and climatic factors on the efficiency of an infiltration basin. Our framework relies on novel analytical solutions that relates the geometrical and hydrological features of the infiltration basin to its efficiency and groundwater contamination risk. The solutions incorporates the randomness associated with inflows (precipitation) and soil properties. We explore the trade‐off between efficiency and the risk of contamination and delineate a design procedure that balances these two opposing needs. Although the framework relies on simplifying assumptions, it provides a computationally efficient manner to obtain physical insights and relate model input parameters to decision making.